Respuesta :

Answer:

(0, 2)

Step-by-step explanation:

Substitution would be a good way of solving these simultaneous equations.  Replace the 'x' in the second equation by ' -y + 2, ' which comes from the first equation.  Then we have:

3y + (-y + 2) = 6.

Simplifying this, we get:

3y - y + 2 = 6, or

2y = 4,

or y = 2.

Now let's find x by substituting 2 for y in the first equation:

x = -(2) + 2 = 0.  So x = 0.

The solution is the point (0, 2).  Note that the second equation is true if we let x = 0 and y = 2.